Fostering Critical Thinking Through Interactive Multimedia: A PBL Approach with Balinese Local Wisdom - Ni Made Teja Pratiwi; I Gede Margunayasa; Luh Putu Sri Lestari (Thinking Skills and Creativity Journal, 2024)
The low critical thinking ability of elementary school students in the subject of IPAS (Integrated Science and Social Studies) is attributed to teaching methods that primarily emphasize rote memorization without incorporating problem-solving activities, particularly those related to real-life environmental issues. This study aims to develop interactive learning multimedia based on the problem-based learning (PBL) model with a focus on Balinese local wisdom to enhance the critical thinking skills of fifth-grade elementary school students in the topic Indonesiaku Kaya Alamnya (My Indonesia, Rich in Natural Resources). The research follows the ADDIE model. Data collection methods employed in this study include tests and questionnaires. The findings of the media validation test indicate a feasibility index of 4.73 for media quality and 4.6 for content quality, both of which fall into the "very good" category. Additionally, the analysis conducted by expert practitioners revealed that the practicality scores obtained were 94% for teachers and 94.4% for students, categorizing the multimedia as highly practical. The effectiveness test results showed a significance level of < 0.01, indicating a significant difference in students' critical thinking abilities before and after using the multimedia. Thus, it can be concluded that the interactive learning multimedia based on the PBL model, incorporating Balinese local wisdom, is both feasible for classroom use and effective in helping students connect conceptual material with real-world situations in their environment.